HOWTO DETECT GOING CONCERN AUDIT OPINION BY USING FINANCIAL REPORT? - ALAMSYAH, SUSTARI; HAMDANI, HAMDANI (S1 Accounting Program, Universitas Pamulang, 2018)
This research aims to examine and analyze the influence of internal factors such as profitability, liquidity, solvency, and cash flow on going concern audit opinion, because companies that accept going concern audit opinion may result in declining stock prices, the fall of the company’s image, distrust of creditors, investors. Suppliers, etc.This research uses quantitative descriptive approach with causality relationship between each variable. The data used in this research is secondary data in the form of financial report of manufacturing companies with sampling technique using purposive sampling and data analysis technique used is logistic regression.The result of this research showed that the independent variables simultaneously affect the dependent variables.Partially, solvency, liquidity, and cash flow have an effect on going concern audit opinion, while the profitability has no effect on going concern audit opinion. The research findings show that the financial ratios can be used to detect the giving of going concern audit opinion